Rehabilitasi Pecandu Narkotika melalui Konsep Pendidikan Islam Menurut Al-Ghazali: Rehabilitation of Narcotics Addicts through the Concept of Islamic Education According to Al-Ghazali - Saefulloh, Ahmad; Nurhakim, Moh.; Khozin, Khozin; Nalus, Syafrul (Anterior Jurnal, 2024)
This research aims to examine and analyze the implementation of rehabilitation for narcotics addicts based on the concept of Islamic education according to Imam Al Ghazali at IPWL Bahrul Maghfiroh, Malang City. The research was conducted qualitatively using a phenomenological approach with purposive sampling techniques through interviews with Rehabilitation Home Assistants, Guardians of Addicts, and Representatives of Addicts who are currently undergoing or have completed the rehabilitation period. The research results show that Therapeutic Community (TC) is the main program at IPWL BMCI Malang City based on Islamic education through an Islamic emotional approach because it prioritizes environmentally friendly therapy. The TC concept applied is Al-Ghazali's educational concept within the scope of Hablumminallah and Hablumminannas. The Hablumminallah concept can be seen in the principle of Man Helping Man to Help by the Mujahadah Principle, the Recovery Concept by Tadzkiyatun Nafs, as well as the Right Living concept by Al-Ghazali's Educational Curriculum Principles, namely that they are both oriented towards a straight approach to Allah. The problem with the Islamic education-based Therapeutic Community program is that the companion cannot know the truth of the expressions expressed by the rehab students as a whole, the companion can only detect changes in behavior and prevent behavior that will arise from signs obtained through information extracted after counseling. personally.